On Counseling in Hong Kong: Can Person-centered Approach Fit in the Hong Kong Culture? - Leung, Wing Sum (2012)
The current study aims to investigate whether the person-centered approach as a western model is an appropriate counseling orientation within Hong Kong, a specific East-Asian context. The study is a literature review on the person-centered counseling’s application in Hong Kong in light of investigation of the Hong Kong culture and counseling profession; a phenomenological account will also be provided on evaluating person centered philosophy and Chinese philosophy. Accordingly the research focus will be in five parts: first, an introduction on the person-centered approach, and summary on the development of Hong Kong counseling profession; second, an overview on the current counseling profession, including counseling training programs, service and the exploration on adopting indigenous and modified western approaches; third, investigation on Hong Kong’s multicultural background and their influences on cultural conflict. A composite depiction is put forward to provide a deeper understanding on cultural conflict; fourth, investigation on the philosophy of person-centered approach and its link with the Chinese philosophy. The great similarity in between on humanism implies the universality of humanism, thus the values of person-centeredness is put forward to resolving cultural conflict. Furthermore, the research implies the support of the promotion of the approach in Hong Kong, thus research direction on modifying the person-centered approach to a culturally friendly approach is put to further research; the last section will discuss on the current practical issue/challenges of the current counseling profession in Hong Kong, before the person-centered approach can be promoted in Hong Kong, and suggestions on the improvement are given.